Pensamento e letramento estatístico: uma investigação a partir do desenvolvimento de um projeto em uma escola da zona rural no município de Itabaiana/SE - Santos, Marcela Lima (2023)
The relevance of statistics to the exercise of citizenship is well known. Every day we see a huge amount of information in the media, combined with the use of statistical tools, requiring contemporary citizens to master statistical knowledge in order to understand it, position themselves critically and make decisions in the face of the information disclosed. In view of this, it is important that, when teaching statistical concepts, students are placed in situations that require them to read and interpret data using tables and graphs, as well as knowledge of other statistical elements for the development of their basic education. These and other issues were discussed by a Discussion Group made up of researchers, primary school teachers and undergraduate and postgraduate students from three Brazilian states: Sergipe, São Paulo and Rio Grande do Sul. In view of the discussions that took place among the teachers from the state of Sergipe, they saw the development of a proposal with the aim of inserting students into an investigative context based on a topic of interest to them as a favorable possibility. It was therefore decided to develop a project at the school on the use of pesticides. In this sense, this investigation analyzed the contributions to the teaching and learning of Statistics, based on a project developed by Basic Education teachers, participants in a Discussion Group, together with students from a school in the rural area of the municipality of Itabaiana/SE. The teachers taking part in this group were primary school teachers (6th to 9th grade) and secondary school teachers from the municipality of Itabaiana/SE. Field diaries were used as instruments for data collection, with records made during discussion meetings and the application of questionnaires. This study was based on a qualitative approach with a bibliographic and documentary nature, as well as procedures involving field research and participant observation. Among the results obtained, it was identified that the project on the use of pesticides was based on a theme chosen by the students because it was an issue that was present in their realities and emerging in that region. In addition, the discussions that took place among the Discussion Group enabled a connection to be made between the discourses produced and discussed collectively, which is justified in the interference of actions in the classroom, in this case through the development of the project. At first, we relied on the development of students' statistical literacy from Gal's perspective (2000, 2002), but based on the discussions, planning and organization of the learning situations for the project, it became necessary to broaden the analysis by considering the dimensions of statistical thinking (investigative cycle and types of thinking), according to Wild and Pfannkuch (1999). In this way, the learning situations mediated by the teachers and developed by the students, unconsciously and naturally, followed the stages of the investigative cycle. The students, in turn, were the protagonists of this process, producing and collecting data. It is worth emphasizing that this action contributed to raising awareness about the use of pesticides, in order to ensure a better quality of life.